Making death, compassion and partnership 'part of life' in school communities. (3rd April 2017) - Kennedy, Carla Jane; Keeffe, Mary; Gardner, Fiona; Farrelly, Cathleen
Abstract: Death can be considered a social taboo, a common source of fear and public avoidance. School communities are not immune to this, as the topic of death is constantly avoided. It is vital to understand how we can socially and culturally cultivate a positive regard for death, dying and bereavement in our school communities. Community members need to discuss these difficult issues and use strategies to enhance compassion, connectedness and support. In this literature review we reason that death is specifically not 'part of life' in school communities. Due to the dearth of school community-based literature on this issue and the progressive literature residing in palliative care, we aim to coalesce palliative care and school-based research, evaluate it and highlight compassion and partnership as a way forward for school communities. Essentially, our societal attitudes about death and dying have been profoundly altered and our community ownership of these normal life events has largely disappeared. This is demonstrated for example, by palliative care moving from the social grass roots 'modern hospice movement' formed in the 1960s and being reintegrated into the mainstream health care system by the end of the 1990s, resulting in an overall medicalised morphing of death, dying and bereavement issues. Therefore, we recommend that further research be conducted in how to develop compassionate schools to inform us how death may be continually made 'part of life' in school communities, for the benefit of students, teachers and families alike.